(untitled) (Zien Journal of Social Sciences and Humanities, 2022)
With the efforts of the Jadids, who reformed many aspects of society with both practical and creative activities, travelogues of a specific conceptual purpose, works of a travelogue nature, emerged. This article explains the main purpose, content and peculiarities of Jadid travelogues.